(3cJGH JhajI Gdcjd def MQe dMhe GdNjds - (3UdGM GdOjf GdYdGFj , UdGM GdOjf CHh SYjO,J (B761 (3g` s ((3YjSi Hf EHQGgje Hf fGLi GdjeGfi GddfHi GdTGaYi s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg ehVM YGde GdSHd hejSQgG aEf eSCdI Ccd dMheGdNjd JaQbJ ajgG GdePGgH hbaJ ajgG Ydi cdGe eHShW Ydbg GdbGVi TeS GdOjf GdSQhLi GdMfai Ydi eG cJHg ai Pdc GdYdGeI Hf GdQGaYI s
(3BNQgG (B:s
(3adG jSJbje gPG GdOdjd Ydi GdeNGda dg , hGddg SHMGfg CYde BNQ cJGH Jhajg Gdcjd bGd eDda (B: (3aQZ efg cJGHI hJUfjakG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B321 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B126s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs